Plant Photoreceptors in Photomorphogenesis and Thermomorphogenesis: Mechanistic Insights: A Literature Review - Fathrissa Amal Syifa; Fiona Zhafirah; Miftahatil Jannah; Rahima Taher; Putra Santoso; Muhammad Idris (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Light and temperature are major environmental factors that shape plant growth and development through interconnected signaling networks. Photomorphogenesis is regulated by photoreceptors, whereas thermomorphogenesis represents developmental adjustment to elevated ambient temperature. This narrative literature review synthesized peer-reviewed studies published from 2002 to 2025 and retrieved from PubMed, ScienceDirect, SpringerLink, Wiley Online Library, Nature, MDPI, Frontiers, and Google Scholar based on their relevance to photoreceptor-mediated light and temperature signaling. The review compares the roles of phytochrome, cryptochrome, phototropin, and UVR8 in photomorphogenesis, thermomorphogenesis, and thermosensing. Available evidence identifies phytochrome, particularly PhyB, as the best-established direct thermosensor, whereas cryptochrome modulates temperature-responsive growth through PIF4. Phototropin conveys temperature information through the lifetime of its photoactivated LOV state in specific physiological responses, while UVR8 acts predominantly as a negative regulator of thermomorphogenesis. Crosstalk among these photoreceptors converges on PIFs, COP1/SPA, HY5, ELF3, and auxin-related pathways. This integrated signaling framework coordinates developmental plasticity, stress acclimation, and vegetative and reproductive performance under fluctuating environments.